Comprehensively characterize the soybean CAM/CML gene family, as it provides resistance against both the soybean mosaic virus and Cercospora sojina pathogens - Zhang, Chunlei; Wang, Yanbo; Zhang, Ruiping; Yuan, Rongqiang; Zhao, Kezhen; Liu, Xiulin; Wang, Xueyang; Zhang, Fengyi; Lamlom, Sobhi F.; Zhang, Bixian; Ren, Honglei (Frontiers in Plant Science, 2025)
IntroductionCalmodulin (CAM) and calmodulin-like (CML) proteins are essential calcium sensors that mediate plant responses to biotic and abiotic stresses. In soybean (Glycine max L. Merr.), these proteins play critical roles in resistance to multiple pathogens, yet a comprehensive characterization of this gene family and its connection to disease resistance has been lacking.MethodsThis study identified and characterized 113 CAM/CML genes in the soybean genome, including 11 GmCAMs and 102 GmCMLs, through bioinformatic analysis using sequence homology, domain architecture, and phylogenetic approaches. Gene structure analysis, cis-acting element identification, and expression profiling were conducted to examine functional diversification and pathogen response patterns.ResultsPhylogenetic analysis revealed 14 distinct groups with evidence of both ancient and recent gene duplication events contributing to family expansion. Gene structure analysis demonstrated higher conservation among GmCAMs (with all but one containing introns) compared to GmCMLs (70% intronless). Analysis of cis-acting elements indicated enrichment of hormone-responsive elements, particularly those associated with abscisic acid (31.2%) and methyl jasmonate (27.7%) responses. Expression profiling revealed distinct CAM/CML gene expression patterns in response to two major soybean pathogens: Soybean Mosaic Virus (SMV) and Cercospora sojina. We identified 15 GmCAM/CML genes that exhibited significantly altered expression in response to both pathogens, with GmCML23, GmCML47, and GmCAM4 showing the strongest correlation with resistance phenotypes.DiscussionThe expression patterns of these genes were validated in various resistant and susceptible varieties, confirming their potential role in broad-spectrum disease resistance. Our findings offer valuable insights into the evolutionary history and functional diversification of the soybean CAM/CML gene family and identify promising candidates for enhancing soybean resistance to multiple pathogens through molecular breeding strategies.